2021
DOI: 10.1029/2020ja028717
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Observation of an Auroral Dawn Storm With the Hubble Space Telescope and Juno

Abstract: Jupiter's ultraviolet auroras are dominated by the main auroral oval, an almost continuous narrow band or series of bands of emission encircling the magnetic poles of the planet (e.g., Clarke et al., 2004;Grodent et al., 2003). This emission maps to the middle magnetosphere, and is generally believed to be driven by the breakdown in corotation of iogenic plasma at radial distances of several tens of planetary radii (Cowley & Bunce, 2001;Hill, 2001;Southwood & Kivelson, 2001). While the overall morphology of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…Vogt et al (2010) and Vogt et al (2020) identified reconnection events in the middle and outer magnetosphere observed by Galileo and Juno, revealing that a similar LT asymmetry of predominant occurrence at dawn also exists for the reconnection sites. Recently, Yao et al (2020) and Swithenbank‐Harris et al (2021) analyzed the storm‐time dynamics at dawn in the context of auroral emissions, suggesting that inward bursts of energetic electrons and protons associated with reconnection could be linked to common occurrences of auroral dawn storms in Jovian magnetosphere (Grodent et al, 2018). Similar local time asymmetries of storm‐time dynamics and associated injections have also been observed in Saturn's magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Vogt et al (2010) and Vogt et al (2020) identified reconnection events in the middle and outer magnetosphere observed by Galileo and Juno, revealing that a similar LT asymmetry of predominant occurrence at dawn also exists for the reconnection sites. Recently, Yao et al (2020) and Swithenbank‐Harris et al (2021) analyzed the storm‐time dynamics at dawn in the context of auroral emissions, suggesting that inward bursts of energetic electrons and protons associated with reconnection could be linked to common occurrences of auroral dawn storms in Jovian magnetosphere (Grodent et al, 2018). Similar local time asymmetries of storm‐time dynamics and associated injections have also been observed in Saturn's magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous in situ measurements in the dawn-side magnetosphere with Juno and auroral images from the HST showed that dawn storms are associated with reconnection, dipolarization and particle acceleration signatures (Z. H. Yao et al, 2020a, Swithenbank-Harris et al 2021. Observations from Galileo also showed signatures of dipolarization, plasmoid release, and plasma energization in the magnetotail, which were associated with substorm-like events (Ge et al, 2007;Kronberg et al, 2005Kronberg et al, , 2008; Krupp et al, 1998), because of the analogy with similar processes taking place during terrestrial substorms.…”
mentioning
confidence: 88%
“…The first three of these exhibited dawn storms, when the dawnside main emission was significantly brightened. The origin of dawn storms is unclear but recent suggestions relate to nightside reconnection (Swithenbank‐Harris et al., 2021; Yao et al., 2020), rather than more directly to the M‐I coupling current system. The other two excluded images were obtained when Juno was outside of the magnetosphere, such that no simultaneous current measurements could be made.…”
Section: Datamentioning
confidence: 99%